ASCARIS LUMBRICOIDES: EPIDEMIOLOGY, DIAGNOSIS, TREATMENT, AND CONTROL - AL-TAMEEMI, KANAAN; KABAKLI, RAIAAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Although Ascaris lumbricoides is a common intestinal parasite of humans with worldwide distribution causing ascariasis, Ascaris is a neglected disease and still is a burden in developing countries. Furthermore, the parasite’s permanence and prevalence present difficulties in control strategies. Therefore, more research on the mechanisms of resistance to infection is required for reducing prevalence parasite and control of infections.